THE EFFECT OF BRAND IMAGE ELEMENTS ON PRICE PREMIUM AND BRAND LOYALTY OF SAMYANG BRAND INSTANT NOODLE IN SURABAYA - Erviana, Ing; Anandya, Dudi; Indarini, Indarini (Manajemen dan Bisnis, 2016)
This research aims to investigate the positive relationship between brand image’s elements which are brand awareness, perceived quality, country of origin, social image, and uniqueness, to price premium and brand loyalty for Samyang instant noodles purchase in Surabaya. This research showed that brand awareness, perceived quality, and country of origin do not significantly correlated to price premium and brand loyalty while social image and uniqueness correlate positively to price premium and brand loyalty so it can be concluded that only social image and uniqueness which affect price premium and brand loyalty. Samyang’s instant noodle distribution manager in Indonesia need to focus on social image and uniqueness and need to ignore brand awareness, perceived quality, and country of origin to get price premium and brand loyalty.